A Conceptual Framework for Developing Women Social Entrepreneurs in Japan. Issue 2 (May 2020) - Nakamura, Yoshie Tomozumi; Horimoto, Mayuko
The Problem: Limited systematic frameworks exist regarding how women develop social entrepreneurship in Japan and what leads Japanese women to change the way they view the world to do something different by becoming social entrepreneurs. The purpose of this article was to develop a theoretical framework for the development of women social entrepreneurs in Japan. There were two guiding questions in this study: How and in what ways women social entrepreneurship are developed in Japan? and What life events affect the values and beliefs that drive them to take authentic entrepreneurial careers for social change? The Solution: We explored the connection between women social entrepreneurship, authentic leadership, and transformative learning theories in the context of Japan through an extensive literature review. The proposed theoretical framework could be used to show the role of critical reflection in face of triggering life events and factors that support or hinder in becoming women social entrepreneurs. The Stakeholders: We focused on Japanese women whose social enterprises aim for social benefits operating through a variety of forms including not-for-profits (NPOs), small businesses, cooperative organizations, and worker collectives.